Radiological and clinical features of multinodular and vacuolating neuronal tumor (MVNT) - Erhan Biyikli; Meltem Kursun; Dogukan Altuntas; Yasar Bayri; Feyyaz Baltacioglu (Egyptian Journal of Neurosurgery, 2023)
Abstract Background To investigate the imaging findings and clinical features of multinodular and vacuolating neuronal tumor (MVNT). Methods We retrospectively sought for cases that have suspicious imaging findings for MVNT through the hospital information system. The patients’ demographics and clinical symptoms were extracted. All available images were re-examined. Results Headache was the most common complaint (n = 7). Other complaints included seizure, stroke-like symptoms and numbness. Conventional MRI revealed that all lesions consisted of tiny, sharply marginated, round or ovoid nodules following the gyral contour. These nodules were hyperintense on T2 and FLAIR WI, hypointense on T1 WI. All lesions were characterized by a lack of enhancement and diffusion restriction. Mass effect and peripheral edema were not observed. MVNT presented as an incidental finding in one case who complained gynecomastia and had pituitary adenoma on pituitary MRI. All lesions were supratentorial—mostly on the right side (10/11)—and located in subcortical white matter. Follow-up MRI was available for 11 patients with a mean of 14.8 months (3–40 months). No change in lesion size and morphology was observed in these follow-up images. Conclusions Radiological and clinical follow-up data suggest MVNT may exhibit indolent behavior. If asymptomatic, patients can be followed by imaging alone. Surgery should be considered for symptomatic patients.